Assessment of copper and zinc concentration in paddy cultivated area at Kota Setar District, Kedah / Qamarul Fakhri Azalan - Azalan, Qamarul Fakhri (Faculty of Plantation and Agrotechnology, 2018)
Copper and zinc plays an essential part for the growth of paddy. Paddy absorbs the nutrients that are in available form from soil. Although it is usually exist in a small amount, the availability of copper and zinc can be excessive if the soil is exposed to several factors such as daily human activities and industrial activities. This study was conducted to identify the amount of copper and zinc availability from three locations and compare the factors that contribute toward the accumulation of copper and zinc in soil. Samples were collected from three locations that were cultivated by paddy which is an industrial area, a roadside area and an urban area. The soil series that were taken at industrial area and roadside area labelled as Kuala Kedah Series (60% Clay) and urban area is as Urban Series. The mean availability of copper at industrial area is 1.052 mg kg-1, for roadside area is 0.905 mg kg-1 and at urban area is 0.326 mg kg-1, whereas the mean availability of zinc at industrial area is 1.258 mg kg-1, for roadside area is 5.038 mg kg-1 and at urban area is 1.705 mg kg-1. The result shows that the content of copper and zinc at those areas is normal and not exceeding Maximum Allowable Limit (MAL) of heavy metal in soil.